Clinical Performance of Class II Romposite Resins Direct Restorations Related to Restorative Technique - 12 Months Longitudinal Study - Vasile-Denis Mereuţă; Sorin Andrian; Gianina Iovan; Claudiu Topoliceanu; Mihaela Sălceanu; Tudor Hamburda; Ștefan Lăcătuşu (Romanian Society of Oral Rehabilitation, 2012)
The aim of the study was to assess the clinical performance of class II composite resins restorations performed using different restorative techniques. Materials and methods The study group included 37 patients aged between 18-42 years. A number of 60 class II direct restorations were performed by a single practitioner using adhesive preparation design with margin bevelling and hybrid composite resin Herculite XRV (Kerr) as restorative material. The teeth included in the study were divided in three groups (n=20) accordingly to restorative technique: I. centripetal build-up; II. oblique layering technique; III. horizontal layering technique. The class II composite resins restorations were assessed after 12 months using United States Public Health Services (USPHS) criteria. Results and discussions The centripetal build-up technique presented the score A for marginal adaptation in 60%, for marginal discoloration in 70% and for anatomical form in 80% of the restorations. The horizontal layering technique presents the score A for marginal adaptation in 40%, for marginal discoloration in 50% and for anatomical form in 50% of the restorations. The oblique layering technique presented the score A for marginal adaptation in 80%, for marginal discoloration in 90% and for anatomical form in 60% of the restorations. Conclusions Statistical differences between groups were found regarding marginal adaptation (oblique layering technique versus horizontal layering technique), marginal discoloration (oblique layering technique versus horizontal layering technique) and anatomical form (centripetal build-up technique versus horizontal layering technique).